Sri Lanka : Improving Access to Financial Services, Selected Issues - World Bank (Washington, DC, 2012)
Sri Lanka has made significant achievements in the provision of financial services in some areas, but there are still critical market segments that remain underserved, especially for small and rural enterprises. Low-income households could also benefit from access to a more diverse set of financial products, such as enhanced remittances and payment services, longer-term savings instruments, insurance products, and improved access to housing finance. The complexity and diversity of the needs suggest that various approaches have to be examined and that a broad range of institutions can be engaged in the delivery of financial services. This report analyzes opportunities for expanding services to key underserved markets. Chapter 2 looks at the expansion of financing opportunities for small businesses. Chapter 3 complements the analysis of Chapter 2 by examining how to improve finance for agriculture through supply chains. Chapter 4 focuses on delivery channels for rural remittances. Remittances to Sri Lanka have been growing rapidly, and the risks posed by informal networks need to be minimized. Moreover, linking migrants to formal financial institutions will yield additional benefits by exposing them to a broad range of financial services (such as savings, credit, and insurance) that can help them manage their economic risks better. Chapter 5 explores the potential role of the postal network in broadening access to financial services in rural areas. Chapter 6 summarizes the main findings of the report.